STATUS ZINC PADA LANSIA LAKI-LAKI YANG ANEMIA DAN TIDAK ANEMIA DI DESA DAN KOTA - Rosmalina, Yuniar; Permaesih, Dewi; Ernawati, Fitrah (PERSATUAN AHLI GIZI INDONESIA, 2004)
ZINC STATUS OF ANEMIC AND NON-ANEMIC MALE ELDERLY IN RURAL AND URBAN AREASThe elderly peoples are prone to micronutrients deficiency such as zinc. The impact of low intake of zinc is impaired functions of wound healing, immunity and taste and smell. The article presents the zinc state of elderly people with or without anemia. The age of subjects was 60 – 75 years. physically and clinically healthy, and agreed to participate in this study. Data collection including anthropometric measurements (body weight, height, mid-upper circumference), zinc, and Hb. Body Mass Index was calculated using ratio body weight to height. Hemoglobin level was analyzed using cyanmethemoglobin method and serum zinc was analyzed using Atomic Absorption Spectrophotometer method. The average Body weight, height and MUAC of urban elderly were statistically higher compared to rural elderly. The proportion of anemic among elderly in rural was 29.0 percent and 15.7 percent in urban. Serum zinc level showed that the proportion of elderly who have low serum zinc level was higher in rural compared to urban area (76.0% vs 54.9%). Out of 54 elderly whose anemic 87.1 percent have serum zinc level below 70 mg/L, while in urban area out of 64 anemic elderly 68.8 % have serum zinc level below 70 mg/L.The proportion of elderly who have suffered anemia and have low serum level were higher in rural compared to urban area.Keywords: anemia, zinc, elderly